2011
DOI: 10.1111/j.1399-3054.2011.01498.x
|View full text |Cite
|
Sign up to set email alerts
|

The family of maize D‐type cyclins: genomic organization, phylogeny and expression patterns

Abstract: Cyclin proteins, associated to cyclin-dependent kinases (CDKs), play fundamental roles in cell cycle control as they constitute a very important driving force to allow cell cycle progression. D-type cyclins (CycDs) are important both for interpreting external mitogenic signals and in the control of the G1 phase. The maize (Zea mays) genome appears to contain at least 17 different CycD genes, and they fall into the subgroups previously described for other plants. Maize CycDs have been named according to identit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
1
32
1
1
Order By: Relevance
“…Maize cells contain 17 genes that encode D-type cyclins, and 15 of them are expressed during germination (Buendía-Monreal et al , 2011). To study the expression at the protein level, and their function during maize germination, antibodies against CycD4;2 or against CycD5;3 were used; the anti-CycD4;2 antibody recognized a 41kDa protein that was present in embryo axes of dry seeds and levels peaked at 18h of germination, to be reduced to about half that value at 24h (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maize cells contain 17 genes that encode D-type cyclins, and 15 of them are expressed during germination (Buendía-Monreal et al , 2011). To study the expression at the protein level, and their function during maize germination, antibodies against CycD4;2 or against CycD5;3 were used; the anti-CycD4;2 antibody recognized a 41kDa protein that was present in embryo axes of dry seeds and levels peaked at 18h of germination, to be reduced to about half that value at 24h (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Maize cells contain 17 different genes coding for D-type cyclins, 15 of which are expressed during germination (Buendía-Monreal et al , 2011); three of them have also been studied at the protein level (Gutiérrez et al , 2005; Lara-Núñez et al , 2008). The aim of this work was to study complexes formed by three maize cyclins—CycD2;2 (a or b, 94% identical), CycD4;2, and CycD5;3 (a or b, 74% identical) with CDKs (types A and B1;1) during the early stages of maize germination, following D-type cyclin protein levels, the type of complexes formed between different cyclins and CDKs, and their activity during maize germination.…”
Section: Introductionmentioning
confidence: 99%
“…edu/annotation_pseudo_apk.shtml). Predicted cyclins (Hu et al, 2010) were added to the list, as well as genes reported to be involved in cell cycle regulation in previous publications (Sauter et al, 1998;Dresselhaus et al, 1999bDresselhaus et al, , 2006Buendía-Monreal et al, 2011;Dante et al, 2014). Finally, the DNA replication-indicating genes encoding proliferating cell nuclear antigen and MCM homologous proteins were added to the list manually based on Ensemble plants (www.plants.ensemble.org) (Sabelli et al, 2009).…”
Section: Cell Cycle Gene Listmentioning
confidence: 99%
“…All related genes were first cloned using KOD enzymes (Toyobo, Osaka, Japan). The maize cell cycle genes, D-type cyclins (AF351190.1; AF351189.141), A-type CDKs (M60526.1, ZmCDKA1; GRMZM2G143213, ZmCDKA2 42; GRMZM2G174596, ZmCDKA336), and B-type CDK (GRMZM2G495626)36) were cloned from the cDNA using gene-specific primers containing NdeI and BamHI restriction sites. The putative ICK/KRP genes were cloned with primers containing NdeI and SalI restriction sites (Table S3).…”
Section: Methodsmentioning
confidence: 99%